Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5194/hess-24-4189-2020
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven estimates of evapotranspiration and its controls in the Congo Basin

Abstract: Abstract. Evapotranspiration (ET) from tropical forests serves as a critical moisture source for regional and global climate cycles. However, the magnitude, seasonality, and interannual variability of ET in the Congo Basin remain poorly constrained due to a scarcity of direct observations, despite the Congo being the second-largest river basin in the world and containing a vast region of tropical forest. In this study, we applied a water balance model to an array of remotely sensed and in situ datasets to prod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 134 publications
3
45
0
Order By: Relevance
“…The decreasing trend in the Congo Basin is detected in ERA5 and MERRA-2, while an opposite one is observed in GLEAM3.2a. Burnett et al (2020) found the Congo Basin had become sunnier and less humid in recent years through the analysis of environmental data. In general, GLEAM ET is fairly close to land ET in tropical Africa (Schuttemeyer et al, 2007;Opoku-Duah et al, 2008;Andam-Akorful et al, 2015;Liu et al, 2016), while MERRA-2 ET has the maximum temporal variability over the Congo Basin (Burnett et al, 2020;Crowhurst et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreasing trend in the Congo Basin is detected in ERA5 and MERRA-2, while an opposite one is observed in GLEAM3.2a. Burnett et al (2020) found the Congo Basin had become sunnier and less humid in recent years through the analysis of environmental data. In general, GLEAM ET is fairly close to land ET in tropical Africa (Schuttemeyer et al, 2007;Opoku-Duah et al, 2008;Andam-Akorful et al, 2015;Liu et al, 2016), while MERRA-2 ET has the maximum temporal variability over the Congo Basin (Burnett et al, 2020;Crowhurst et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Burnett et al (2020) found the Congo Basin had become sunnier and less humid in recent years through the analysis of environmental data. In general, GLEAM ET is fairly close to land ET in tropical Africa (Schuttemeyer et al, 2007;Opoku-Duah et al, 2008;Andam-Akorful et al, 2015;Liu et al, 2016), while MERRA-2 ET has the maximum temporal variability over the Congo Basin (Burnett et al, 2020;Crowhurst et al, 2020). The increase in the east of North America, west of Europe and south of Asia is detectable in all datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found a higher ET contribution to the moisture budget during the spring rainy season compared to that of the fall rainy season, which could also help explain why ET contributes more moisture for the spring rainy season. On the other hand, Burnett et al (2020) calculated basin-scale ET in the Congo using water-balance methods, positing that increased radiation, as well as the availability of soil moisture, can explain increased ET in the spring: Higher direct photosynthetically active radiation (PAR) fractions combined with higher net solar radiation increase water use efficiency, while increased terrestrial water storage increases the amount of water available for transpiration. Crowhurst et al (2020), using global climate models, also calculated ET over a similar domain and found that it was higher in the spring rainy seasons compared to the fall rainy season.…”
Section: Discussionmentioning
confidence: 99%
“…10.1029/2020JG006024 7 of 14 Figure 4b shows the contributions of ET and MFC to precipitation within our Congo domain, as indicated by ET/P and MFC/P. ET/P shows consistently high values throughout the year and MFC/P is always lower than that of ET/P (e.g., Burnett et al, 2020;Crowhurst et al, 2020). These data support our conclusion that there is a larger relative contribution of ET to the moisture for the spring versus fall rainy seasons.…”
Section: Precipitation and Dmentioning
confidence: 99%
“…Finally, comparing different methods, the results demonstrated that combination performance based on EIVD method generally outperformed other methods through synthetic experiments. As for the simplest averaging method, though previous studies recommended the average value as the proxy of reference (Pan et al, 2020;Burnett et al, 2020;Baker et al, 2021), our synthetic results demonstrated that the averaging method presented the lowest improvement. For gridded data, the equal weight for each grid assigned by averaging method ignored the spatial variability of different products, which could result in large uncertainty.…”
Section: Synthetic Experiments Results 380mentioning
confidence: 77%